Research and training priorities of staff supporting individuals with intellectual disabilities with or without autism. Issue 3 (11th January 2022) - Simpson, Kate; Adams, Dawn; Manokara, Vimallan; Malone, Stephanie
Abstract: Research and training priority setting can help to direct limited resources to areas, which will have maximum benefit in improving the skills and knowledge of support workers to better meet the needs of their clients. Staff from a multi‐site organisation in Singapore that supports individuals with intellectual disability and/or autism completed a questionnaire identifying their research and training practices and priorities. Staff were asked to identify their access to training and research, and what they viewed as priorities in these areas. They also completed a Likert scale questionnaire on training and research priorities identified from previous research. Response rate was 27.8% ( n = 82). Analyses found that staff were more likely to rely on training than research to inform their knowledge, with training in understanding and managing behaviours identified as a priority across the organisation. Staff identified interventions and supports for caregivers as a research priority. The consensus with previous research would suggest that there are training needs and research areas, which may inform global priorities for this population.